DUGAAN PRAKTIK MONOPOLI PENGGUNAAN LinkAja SEBAGAI PEMBAYARAN PEMBELIAN TIKET KERETA API LOKAL PADA APLIKASI KAI Access - Agustin, Isna Yulia (Private Law Department, Faculty of Law, University of Jember, Indonesia, 2023)
ABSTRACT: An electronic wallet is an application that is used to store electronic money and can be used to make digital payments. In Indonesia, along with the times, there are various kinds of electronic wallet applications, one of which is LinkAja. LinkAja can be used to make payments for purchasing local train tickets on the KAI Access application. In the KAI Access application, there are two types of train tickets, namely intercity train tickets and local train tickets. The use of LinkAja as a payment method in purchasing local train tickets on the KAI Access application causes problems. Local train tickets only provide a payment method using LinkAja, while intercity train tickets provide several payment method options. This of course raises an allegation of monopolistic practice. KPPU as an independent institution established to oversee business competition in Indonesia, through its press release No. 28/KPPU-PR/V/2020 has warned to promote fair business competition. The research method used is doctrinal, which focuses on the study of the application of norms or rules related to the problems in this research. The results of the study concluded that the legal basis for using LinkAja as a payment method in purchasing local train tickets on the KAI Access application is referring to Bank Indonesia Regulation Number 18/40/PBI/2016 concerning the Implementation of Payment Transaction Processing, which states that electronic wallets are used to make payments. payment transactions. LinkAja's action on the control of local train ticket payment services on the KAI Access application can be said to be a monopoly act because it has violated the elements contained in Article 17 of Law No. 5 of 1999.